2018
DOI: 10.3390/app8122362
|View full text |Cite
|
Sign up to set email alerts
|

III-Nitride Short Period Superlattices for Deep UV Light Emitters

Abstract: III-Nitride short period superlattices (SPSLs), whose period does not exceed ~2 nm (~8 monolayers), have a few unique properties allowing engineering of light-emitting devices emitting in deep UV range of wavelengths with significant reduction of dislocation density in the active layer. Such SPSLs can be grown using both molecular beam epitaxy and metal organic chemical vapor deposition approaches. Of the two growth methods, the former is discussed in more detail in this review. The electrical and optical prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 128 publications
(183 reference statements)
0
10
0
Order By: Relevance
“…As a result, the Raman spectra of SLs should contain a set o A1(LO) lines, which are associated with phonons belonging to two high-fr branches (A1(LO) and B1(high)) of phonon dispersion in the Г-A direction of the the inset in Figure 1). The ranges of dispersion of these modes extend from 735 to (2). The inset shows the dispersion range of A 1 (LO) and B 1 (high) phonons of bulk AlN and GaN along the Г-A direction of the BZ [38,39].…”
Section: Raman Spectra Of Pa Mbe-and Movpe-grown Sls and Rei Modelingmentioning
confidence: 99%
See 3 more Smart Citations
“…As a result, the Raman spectra of SLs should contain a set o A1(LO) lines, which are associated with phonons belonging to two high-fr branches (A1(LO) and B1(high)) of phonon dispersion in the Г-A direction of the the inset in Figure 1). The ranges of dispersion of these modes extend from 735 to (2). The inset shows the dispersion range of A 1 (LO) and B 1 (high) phonons of bulk AlN and GaN along the Г-A direction of the BZ [38,39].…”
Section: Raman Spectra Of Pa Mbe-and Movpe-grown Sls and Rei Modelingmentioning
confidence: 99%
“…Therefore, extended GaN/AlN SLs have been included in various photodetecting and light-emitting infrared devices based on intersubband transitions [ 1 ]. Quantum wells (QWs) based on layers of GaN compounds in a wider gap AlN matrix and GaN/AlN SLs are considered for use in the architectures of many optoelectronic devices in the ultraviolet (UV) range as active regions [ 2 ] or reflective Bragg mirrors [ 3 ]. Many problems in the production of high-performance UV lasers and light-emitting diodes can be solved, inter alia , through the use of extended GaN/AlN SLs (also called digital solid solutions, or digital alloys), which provide doping of the emitter layers with a high average Al content (>40 mol%) [ 2 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…AlN/AlGaN SLs are multiple heterojunction structures in which different lattice mismatch layers of several tens of angstroms thick are repeatedly grown, and it has been reported that the insertion of these layers can relieve and control the strain. [33][34][35][36] Some causes of strain relaxation due to the insertion of AlN/AlGaN SLs structures have been suggested: the occurrence of defects, the formation of local cracks, and the prevention of pseudomorphic growth. [33][34][35][36] In SLs, opposite strains applied to a very thin layer are balanced and play a role of controlling the strain of the later growing layers.…”
Section: Depth Profiling Of Each Layer Of the Truncated Samplementioning
confidence: 99%